THE DEVELOPMENT OF NUMBERS AND STRUCTURES OF VEHICLES IN SLOVAK REPUBLIC - Gnap, Jozef; Konecny, Vladimir; Simkova, Ivana (Doprava a spoje, 2012)
This article deals with finding solutions concerning the development of numbers and structures of vehicles in Slovak Republic and the development of traffic infrastructure and partly also the influence on the environment and other factors. An issue was also assessed respecting the objectives formulated in White Paper of the European Union "Plan of uniform European area - creating a competitive traffic system using resources efficiently".